2001
DOI: 10.1103/physrevb.63.165211
|View full text |Cite
|
Sign up to set email alerts
|

Local atomic strain inZnSe1xTexfrom high real-space resolution neutron pair distribution function measurements

Abstract: High real-space resolution atomic pair distribution functions ͑PDF's͒ have been obtained from ZnSe 1Ϫx Te x using neutron powder diffraction. Distinct Zn-Se and Zn-Te nearest-neighbor ͑nn͒ bonds, differing in length by ⌬rϭ0.14 Å, are resolved in the measured PDF's, allowing the evolution with composition of the individual bond lengths to be studied. The local bond lengths change much more slowly with doping than the average bond length obtained crystallographically. The nn bond-length distributions are constan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…For an immediate comparison with the random alloys, the nearest-neighbor local Fe–Se and Fe–Te distances in the FeSe 1− x Te x ternary system are plotted as a function of Te concentration in figure 7. The behavior is similar to the so-called Z -plot, characteristic of the nearest-neighbor distances in ternary alloys [5761]. It is clear that the local Fe–Se and Fe–Te bond lengths are closer to those in the binary end members (FeSe and FeTe) than what one expects from the prediction of Vegard's law [49].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…For an immediate comparison with the random alloys, the nearest-neighbor local Fe–Se and Fe–Te distances in the FeSe 1− x Te x ternary system are plotted as a function of Te concentration in figure 7. The behavior is similar to the so-called Z -plot, characteristic of the nearest-neighbor distances in ternary alloys [5761]. It is clear that the local Fe–Se and Fe–Te bond lengths are closer to those in the binary end members (FeSe and FeTe) than what one expects from the prediction of Vegard's law [49].…”
Section: Resultssupporting
confidence: 55%
“…Indeed, the situation is similar to random alloys of the type AB 1− x C x in which local structure around the A site is not homogeneous although the end members AB and AC possess perfect crystallographic symmetry [5761]. Indeed, the bond lengths A–B and A–C are non-equivalent and hence the bond angles are also so.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This method is typically used on highly crystalline systems, such as to study chemical ordering [262] and local strain. [263] Many nanoparticle systems can be modelled as a finite object cut out of a bulk atomic structure, by calculating the bulk structure using a small-box model and then applying a shape function averaged over all directions, which has the effect of applying a damping envelope to the data. [126,264,265] However, in cases where there is significant disorder or structural rearrangement of the atoms on the nanoparticle surface, such methods may fail or yield a size that is less than the true Downloaded by [New York University] at 06:05 08 June 2015 nanoparticle size.…”
Section: Pair Distribution Function Analysismentioning
confidence: 99%
“…It is evidently very important to have accurate local structural information of these systems. Details of this study can be found in Peterson et al (2001). For the purpose of this paper, we concentrate on the nearest neighbor (NN) peak.…”
Section: Short Range Structurementioning
confidence: 99%